2021
DOI: 10.1111/jam.15063
|View full text |Cite
|
Sign up to set email alerts
|

Root endophytic fungus Serendipita indica modulates barley leaf blade proteome by increasing the abundance of photosynthetic proteins in response to salinity

Abstract: Aims The present study aimed at analysing the proteome pattern of the leaf blade of barley (Hordeum vulgare L.) in Serendipita indica‐colonised plants to decipher the molecular mechanism of S. indica‐mediated salt stress. This work is aligned with our previous research on barley leaf sheath to study proteomic pattern variability in leaf blade and sheath of barley plant in response to salinity and S. indica inoculation. Methods and Results The experiment was conducted using a completely randomised factorial des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 84 publications
(97 reference statements)
2
7
0
Order By: Relevance
“…In accordance with the current results, it has also been reported that P. indica-colonized barley cultivated under 300 mM NaCl had enhanced K + and lower Na + ion content in the leaves, as compared with non-colonized plants (Deshmukh et al, 2006). Furthermore, decline in the Na + content with the P. indica cocultivation of Arabidopsis and barley were also reported under salt stress (Lanza et al, 2019;Sepehri et al, 2021). In relation to the present study, increased K + ion content in the shoots of tomato plants inoculated with P. indica was also associated with its salinity tolerance (Yun et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the current results, it has also been reported that P. indica-colonized barley cultivated under 300 mM NaCl had enhanced K + and lower Na + ion content in the leaves, as compared with non-colonized plants (Deshmukh et al, 2006). Furthermore, decline in the Na + content with the P. indica cocultivation of Arabidopsis and barley were also reported under salt stress (Lanza et al, 2019;Sepehri et al, 2021). In relation to the present study, increased K + ion content in the shoots of tomato plants inoculated with P. indica was also associated with its salinity tolerance (Yun et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, nitrogen metabolism, carbon fixation, and glyoxylate metabolism was also significantly enriched, and a similar observation was made in barley under salt stress in the presence of endophytic fungus [ 47 ]. Besides the proteins involved in nitrogen metabolism, many other proteins were also differentially expressed, including phosphoesterase, calcium-dependent protein kinases, pathogenesis-related proteins, peroxidases, multicopper oxidase, chitinase, aminotransferase, and o-methyltransferase.…”
Section: Resultssupporting
confidence: 55%
“…LHC‐I, LHC‐II, PSBO (oxygen‐evolving enhancer protein 1), PSAK (photosystem I reaction center subunit K), PSAG (photosystem I reaction center subunit V), and so forth, in barley indicated toward the protective role of the mutualistic interaction of the fungal endophyte with the barley roots. Similarly, the endophyte fungus— Serendipita indica was shown to enhance the proteins associated with carbohydrate metabolism and photosynthesis in barley plants under salinity stress (Sepehri et al, 2021).…”
Section: Molecular Mechanism Of Plant Salt‐tolerance Induced By Microorganismsmentioning
confidence: 99%